Phototrophic bioplastic production from domestic and agro-industrial wastewaters - Almeida, Juliana Roda (2017)
Polyhydroxyalkanoates (PHA), are a biodegradable polymer, naturally synthesized by several bacteria and with similar characteristics to conventional plastics. Recently, phototrophic PHA production has also been achieved in photosynthetic mixed cultures (PMCs) under an open, non-aerated and using direct sunlight system, lowering the operational costs commonly associated to the PHA production by pure and aerated mixed cultures. The photo-bioreactors (PBR) are also commonly used as wastewater (WW) treatment systems along with a consortium microalgae and bacteria communities. The main goals of this thesis were precisely to select a PHA accumulating PMC to achieve a new added-value bioproduct. The enrichment process of the PMC was performed by two different selection strategies - permanent feast regime and feast and famine regime - that were carried out under the same operational conditions of High Rate Algae Ponds (HRAPs) from Chiclana Wastewater Treatment Plant, using artificial illumination and fed with real wastewaters, establishing the effect of using wastewater on the culture growth and PHA production stability, and furthermore to evaluate the impact of operational conditions (OLR, pH, temperature and light intensity) on the PHA production performance of the system. This will be the first time that the PHA production through PMC will be tested at demonstration scale and using real wastewater.